Analisis Pengaruh Arus Listrik Pada Proses Pengelasan TIG Terhadap Kekuatan Sambungan Las Material Logam Aluminium 6061 - Ilham Khalilulah; Iwan Gunawan; Ari Siswanto (Jurnal Vokasi Mekanika (VoMek), 2024)
The The selection of current in aluminum welding significantly affects weld joint quality. Excessively high current can lead to increased penetration, distortion, and overmelting. Conversely, low current may result in weak joints, insufficient penetration, and increased porosity risk. This study focuses on understanding the effect of current variations in the Tungsten Inert Gas (TIG) welding process on the strength of 6 mm thick aluminum 6061 welds using ER4043 filler. Tensile strength and flexibility are critical in construction, ensuring strong, stable, and durable welds to withstand static loads. The study found that a welding current of 160A achieved the highest tensile strength, averaging 207.49 MPa. In contrast, 100A yielded the lowest tensile strength at an average of 132.854 MPa, while 130A produced an intermediate average of 154.128 MPa. Bending test results showed that only the 160A weld met standard criteria, whereas welds with 100A and 130A currents exhibited cracks and fractures beyond acceptable limits. Microstructural analysis revealed that the Heat Affected Zone (HAZ) and weld metal at 160A were dominated by the Mg2Si phase, which significantly enhances the mechanical strength of the material. These findings highlight the importance of selecting the appropriate welding current for aluminum 6061. A current of 160A is recommended as the optimal choice to produce strong and reliable weld joints.